2010
DOI: 10.1016/j.rbmo.2010.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Follicular-fluid anti-Müllerian hormone concentration is similar in patients with endometriosis compared with non-endometriotic patients

Abstract: This cross-sectional prospective study assessed follicular-fluid anti-Müllerian hormone (AMH) concentrations in infertile patients with mild/minimal endometriosis during natural IVF. Thirty-two women participated in the study. Patients were divided into two groups: tubal obstruction without endometriosis (control group) and minimal/mild endometriosis (study group). All patients underwent laparoscopy for assessment of infertility; at the same time, any foci of endometriosis found were cauterized. AMH concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
10
0
3
Order By: Relevance
“…However, AMH expression still exists in CCs of the preovulatory follicle with lower expression in GCs, suggesting that these cells still have the capacity to secrete AMH into the FF at these later stages of folliculogenesis (37). Previous studies have demonstrated a positive correlation between FF AMH concentration andsuccessful oocyte fertilization, suggesting that AMH production and activity is reduced in GCs and CCs from these patients (8,37,38). Andersen et al (39) reported that FF FSH can act as a negative regulator of AMH expression; however, in the present study FF FSH and LH concentrations were not different between the groups.…”
Section: Discussionmentioning
confidence: 96%
“…However, AMH expression still exists in CCs of the preovulatory follicle with lower expression in GCs, suggesting that these cells still have the capacity to secrete AMH into the FF at these later stages of folliculogenesis (37). Previous studies have demonstrated a positive correlation between FF AMH concentration andsuccessful oocyte fertilization, suggesting that AMH production and activity is reduced in GCs and CCs from these patients (8,37,38). Andersen et al (39) reported that FF FSH can act as a negative regulator of AMH expression; however, in the present study FF FSH and LH concentrations were not different between the groups.…”
Section: Discussionmentioning
confidence: 96%
“…Shebl et al 15 demonstrated the association between low serum AMH levels and severity of women with endometriosis. In addition, Campos et al 16 showed that patients with minimal to mild endometriosis have similar follicular-fluid AMH concentrations during natural in vitro fertilization (IVF) cycle, as patients with tubal obstruction without endometriosis. Pacchiarotti et al 17 reported that serum AMH levels are reduced in women with endometriosis who have never undergone ovarian surgery, suggesting a state of poor ovarian reserve.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, further research suggested similarities in ovarian reserve in infertility patients with minimal/mild endometriosis compared to patients with tubal obstruction 9. Although a few studies have set out to compare serum AMH level in women with endometrioma and controls before surgery, they have yet to find significant reductions in serum AMH levels in women with endometrioma prior to surgery 10-12…”
Section: Introductionmentioning
confidence: 99%